Depression and sexual dysfunction in patients with chronic low back pain (Annals of Medical Research, 2022)
Aim: Low back pain is pain, muscle tension, or stiffness localized below the costal margin and above the inferior gluteal folds, with or without leg pain (sciatica), and is defined as chronic when it persists for 12 weeks or more. Several studies have addressed the relationship between chronic low back pain and poor sexual activity for over two decades. This study was designed to clarify the relationship between depression and chronic low back pain in light of the information obtained from the literature review and examine how it affects sexual life.Materials and Methods: Eighty people participated in the study. After signing the informed consent form, participants were examined by experienced physicians. Quebec Low Back Pain Scale, Beck's Depression Scale, and Arizona Sexual Experiences Scale (ASEX) were applied to the participants.Results: As a result of the Mann-Whitney U test, which examined whether there was a significant difference in the Arizona Sexual Experiences Scale scores between the case group and the control group, there was a significant difference between the groups (U=256,500, p